ANALISIS NILAI EKONOMI KAYU SENGON DI KECAMATAN MANUHING RAYA, KABUPATEN GUNUNG MAS, KALIMANTAN TENGAH - Rodi, Rodi; Helmi, Muhammad; Hatta, Gusti Muhammad (Lambung Mangkurat University-Indonesia, 2025)
Analysis of the economic value of Albizia chenensis wood needs to be carried out to calculate farmers' profits from selling their wood so that it can be used as a reference in the implementation of farmers' activities in future cultivation when cultivating Albizia chenensis wood until the sales process is accepted by the factory according toGread Log wood. The research was carried out in 5 villages and 1 sub-district, namely Tumbang Mantuhe, Putat Durei, Tumbang Samui, Tumbang Oroi, Luwuk Tukau, and Tehang sub-districts in the Manuhing Raya sub-district, activities were carried out for 3 months from November 2023 to January 2024. Research methods this ispurposive sampling, questionnaires, interviews, and using quantitative and descriptive qualitative field analysis. The results of the research analysis are that the total cost of Albizia chenensis cultivation is IDR. 10,938/stem which consists of fixed costs of Rp. 308/seed and variable costs of Rp. 10,630/stick. The total cost of selling Sengon wood is Rp. 14,950,000/m3 at a price of Rp. 467,187,500/m3 consisting of fixed costs of Rp. 400,000/m3 at a price of Rp. 12,500/m3 and variable costs of Rp. 14,550,000/32 m3 or Rp. 454,687,500,-and the final results received by Albizia chenensis farmers amounted to Rp. 3,373,911 from the sale of 32 m3 of Albizia chenensis wood at a per cubic price of Rp. 96,250,-